From Bait al-Hikmah to Digital Platforms: Continuities in Islamic Knowledge Systems - Rahman, Gohar (Yayasan Sinergi Kawula Muda, 2024)
This study presents a comprehensive narrative review of the enduring contributions of Islamic civilization, focusing on intellectual innovation, institutional development, cultural expression, and global influence. The review aims to synthesize literature across disciplines to understand how Islamic heritage continues to shape modern science, governance, education, and intercultural exchange. Methodologically, the review employed purposive literature selection from databases such as Scopus and Google Scholar using key terms like